Synthesis and characterization of a phosphorous/nitrogen based sol-gel coating as a novel halogen- and formaldehyde-free flame retardant finishing for cotton fabric - Castellano, Angela; Colleoni, Claudio; Iacono, Giuseppina; Mezzi, Alessio; Plutino, Maria Rosaria; Malucelli, Giulio; Rosace, Giuseppe (Polymer degradation and stability, 2019)
A novel formaldehyde- and halogen-free coating, containing phosphorus, nitrogen and silicon, was synthesized with a promising approach to enhance flame retardancy of cotton fabric. To this aim, a new sol-gel precursor, comprising in the same molecule P, N and Si, namely (3-Glycidyloxypropyl triethoxysilane modified N-(phosphonomethyl) iminodiacetic acid (PGPTES), was co-hydrolysed and co-condensated with tetraethylorthosilicate (TEOS), as silane linker, and used for producing a self-extinguishing cotton fabric coating. The structure of PGPTES was characterized by 1H/13C/31P nuclear magnetic resonance and the obtained coating was investigated by FT-Infrared Spectroscopy and Scanning Electron Microscopy. The thermal properties of the treated fabric were studied by Thermogravimetric Analyses and Cone Calorimetry Tests. The obtained results show that the synthetized coating is able to catalyse the dehydration and char formation of cellulose based polymer at a lower temperature, thanks to the thermal decomposition of phosphate giving rise to acidic intermediates, able to further react with cellulose-based fabric, hence improving the flame retardant properties of the latter. •NMR analysis confirms the functionalization of GPTES sol-gel precursor with PMIDA.•PMIDA acts as nitrogen and phosphorous source in the P/N flame retardant synergism.•The concurrent presence of Si, P and N enhances cellulose dehydration mechanism.•The final residue for treated cotton sample, after cone calorimetry test, is 26%.•Self-extinguishing properties are achieved by the treated cellulose-based fabric.